Pars plana vitrectomy relieves the depression in patients with symptomatic vitreous floaters - Wu, Rong-Han (Int J Ophthalmol, 2020)
AIM: To investigate the depressive state among the patients with symptomatic vitreous floaters (SVF), as well as its change after SVF removal via vitrectomy surgery. METHODS: Twenty-eight eyes of 28 patients who underwent 27-gauge pars plana vitrectomy (PPV) for SVF were included. Thirty-nine eyes of 39 age- and gender-matched healthy volunteers without SVF were also recruited as a healthy control. Center for Epidemiologic Studies Depression (CES-D) was used to assess volunteers and patients' depression (before and 1wk after PPV). RESULTS: The CES-D score was 18.3±8.6 for patients, and was 12.4±6.0 for healthy control (P=0.003). Patients were significantly more likely to be in a depressive state (53.6%, defined as CES-D score ≥16) than the healthy control (20.5%, P=0.005). For patients with SVF, the CES-D score was negatively correlated with their age (r(s)=-0.42, P=0.025). After PPV, both the CES-D score (11.9±5.4 vs 18.3±8.6, P<0.001) and proportion of depressive state (18.5% vs 53.6%, P=0.005) were significantly decreased. CONCLUSION: This study suggests that symptoms of vitreous floaters have an apparently negative impact on patients' psychological state. The PPV can effectively relieve the depressive state for patients with SVF.